Computational simulation of rheological blood flow containing hybrid nanoparticles in an inclined catheterized artery with stenotic, aneurysmal and slip effects. (December 2021) - Tripathi, Jayati; Vasu, B.; Bég, O. Anwar; Gorla, Rama Subba Reddy; Kameswaran, Peri K.
Abstract: Influenced by nano-drug delivery applications, the present article considers the collective effects of hybrid biocompatible metallic nanoparticles (Silver and Copper), a stenosis and an aneurysm on the unsteady blood flow characteristics in a catheterized tapered inclined artery. The non-Newtonian Carreau fluid model is deployed to represent the hemorheological characteristics in the arterial region. A modified Tiwari-Das volume fraction model is adopted for nanoscale effects. The permeability of the arterial wall and the inclination of the diseased artery are taken into account. The nanoparticles are also considered to have various shapes (bricks, cylinders, platelets, blades) and therefore the influence of different shape parameters is discussed. The conservation equations for mass, linear momentum and energy are normalized by employing suitable non-dimensional variables. The transformed equations with associated boundary conditions are solved numerically using the FTCS method. Key hemodynamic characteristics i.e. velocity, temperature, flow rate, wall shear stress (WSS) in stenotic and aneurysm region for a particular critical height of the stenosis, are computed. Hybrid nanoparticles (Ag–Cu/Blood) accelerate the axial flow and increase temperatures significantly compared with unitary nanoparticles (Ag/blood), at both the stenosis and aneurysm segments. Axial velocity, temperature and flow rate are all enhanced with greater nanoparticle shape factor. Axial velocity, temperature, wall shear stress and flow rate magnitudes are always comparatively higher at the aneurysm region compared with the stenotic segment. The simulations provide novel insights into the performance of different nanoparticle geometries and also rheological behaviour in realistic nano-pharmaco-dynamic transport and percutaneous coronary intervention (PCI). Highlights: The study shows the effects of hybrid nanoparticles on hemodynamics in a catheterized artery having stenosis and aneurysm. The hybrid nanoparticles are considered to have various shapes and the influence of different shape parameters is discussed. Elevation in slip velocity and Froude number produces axial velocity enhancement at both the stenosis and aneurysm segment. Blood flow characteristics are always comparatively higher at the aneurysm region compared with the stenotic segment. Increasing the arterial inclination angle, velocity is increased and the highest velocity is seized for vertical artery.